Hubungan Kontribusi Energi, Protein, Fe, Vitamin C dan Asam Folat Makan Siang Dengan Kadar Hemoglobin - Indrayanti Ratna Pramesti; Ni Made Dewantari; Ni Made Yuni Gumala (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Women workers are generally at risk of developing iron nutrient anemia, in addition to lack of iron intake into the body which is a factor that causes anemia, generally menstruating every month. Iron deficiency anemia can have an impact on female labor, among others, fatigue, effects on work productivity, and decreased immune system.The purpose of this study was to prove the relationship between the contribution of energy, protein, Fe, vitamin C and folic acid lunch with hemoglobin levels in women workers at the Tjampuhan Ubud hotel.This study used a cross sectional study design with a sample of 40 people. Data collection included Hb levels using secondary data. Data on the contribution of energy, protein, Fe, vitamin C and folic acid were obtained using Google Form, assisted with 2x24 hour recall method and processed using the 2007 Nutrition Survey program. To find out the relationship between the contribution of energy, protein, Fe, vitamin C and folic acid lunch with hemoglobin levels used Pearson correlation statistics test.There is no significant relationship between the contribution of energy, protein, Fe, vitamin C and folic acid lunch with hemoglobin levels (p0.05) at Tjampuhan Hotel Ubud.